Case Study on the Liaison Officer MSMEs Dhira Donut Kentang and Es Teler Tropical - Nazila Mayani (CV. ALIM'SPUBLISHING, 2026)
This research aims to support MSMEs, especially Dhira Donut Kentang and Es Teler Tropical, through the Polbeng Business Expo by improving digital marketing, creating business profiles, product catalogs, promotional videos, and implementing QRIS payment methods. The Expo also helps these MSMEs reach a wider market and increase public awareness of their products. The project uses three stages: preparation, implementation, and accomplishment. The results show that the Liaison Officer plays an important role in connecting MSMEs with potential customers, while the Business Consultant provides useful guidance related to digital marketing and operational improvements. Dhira Donut Kentang and Es Teler Tropical gained several benefits, including increased product visibility on social media, more efficient transactions through QRIS, and better understanding of financial management through structured financial reports. Overall, the Polbeng Business Expo successfully supports the development of MSMEs through innovative and strategic approaches.